Effects of grammarly application on ESL students’ construction of grammatically correct sentences in essay writing - Jayavalan, Kalpana (2017)
The purpose of this study is to investigate how a grammar checker application that is, Grammarly helps the students in constructing grammatically correct sentences in writing essays. In the Malaysian context of English language learning, the major difficulty that the students encounter is writing and it has always been the reason why students cannot excel in the examination (Chuo, 2004). Thus, this study explores the effects of Grammarly, a grammar checker computer application, in aiding secondary students’ in constructing grammatically accurate sentences. The research is guided by the theories and principles of Vygotsky’s (1978) Zone of Proximal Development (ZPD) and Knowles’ (1984) Self-Directed Learning approach. This study employs a quantitative research methodology, which is quasi experimental approach with the non-equivalent control group design. Participants in this study were 60 Form Four students from two different classes in a public secondary school in a state in western part of Peninsular Malaysia. They were divided equally into an experimental and a control group and the students came from the same age group and English language, particularly English writing proficiency. The data was gathered for research through pre-and post-tests which were then analysed using paired sample T-test. Continuous quantitative type of observation data (i.e., scores from writing exercises) were also obtained from their engagement with series of treatment using the Grammarly grammar checker application. The findings revealed that the grammar checker aids the students in order to construct sentences which are grammatically accurate in essay writing. The results of this study revealed that at P<.001 alpha level the grammar checker does aid sentence construction which are grammatically correct when it comes to writing essays among the Form 4 students, particularly on their use of correct grammar functions (namely subject-verb agreement, sentence structure, spelling, and punctuation). The researcher calls for more future research on the grammar checker as it holds an opportunity for the students to progress in their various types of essay writing. It might be a great shift from a traditional learning approach to a more independent self-directed learning approach among students.